HUBUNGAN PENERAPAN MEDIA PEMBELAJARAN E-LEARNING, METODE PEMBELAJARAN BERBASIS PENUGASAN, DAN PERAN ORANG TUA DENGAN HASIL BELAJAR SISWA DALAM MASA PANDEMI COVID-19 - Petrus Bayu Prasetyo; Natalina Premastuti Brataningrum (Universitas Sanata Dharma, 2022)
The research aims to find out whether there is the positive correlation between (1) the implementation of e-learning media and students’ learning results during the Covid-19 pandemic; (2) the task-based learning method and students’ learning results during the Covid-19 pandemic; (3) the role of parents and students’ learning results during the Covid-19 pandemic. The research was a correlational research conducted from April to May 2021. The participants were 256 students at SMK BOPKRI 1 Yogyakarta. The data was collected through a questionnaire and document analysis. The data was then described using the PAP Type II, while the hypothesis was examined using the Spearman Rank. The study revealed that: (1) there is no positive correlation between the implementation of e-learning media and students’ learning results during the Covid-19 pandemic. It is shown by the sig. (1-tailed) = 0.438; (2) there is no positive correlation between the task-based learning method and students’ learning results during the Covid-19 pandemic. It is shown by sig. (1-tailed) = 0.188; (3) there is no positive correlation between the role of parents and students’ learning results during the Covid-19 pandemic. It is shown by sig. (1-tailed) = 0.206.Keywords: The implementation of e-learning media; task-based learning method; parents’ roles; students’ learning results.